(untitled) (Bangladesh Journal of Medical Science, 2017)
Objective: To assess safety and feasibility of completely non-fluoroscopic ureteroscopy for treatment of mid and distal ureteric stone in term of stone free-rate and complications. Material and Methods: Over study period between January 2014 and January 2015, ninety-one complete fluoroscopy-less semirigid ureteroscopies were performed for treatment of symptomatic ureteric stones. Age, sex, stone size, location, side, operative time, auxiliary procedures, stonefree rate and complications, all were assessed. A Stone-free rate was defined as the lack of radiographic evidence of residual stone at 4 weeks. Postoperative imaging, and complications were grading according to modified Clavien classification system, which used initially to grade complications of general surgery. Results: The average age of our subjects was 32.9, with male and right side predominant, 68 % and 64.8% respectively. The average stone size and operative time were 10.07 and 32.08 respectively. Fifty six semirigid retrograde ureteroscopies were done for distal ureteric and 35 for mid ureteric stones, achieving 91.2% stone free rate, with overall intraoperative complications of 18.6%. All cases were managed on day case basis, ureters were stenting preoperatively in 37 patients and all cases were stenting with an appropriate size of double J. Conclusion: Zero fluoroscopic semirigid retrograde ureteroscopy is a safe and feasible treatment modality for management of distal and mid ureteric stones. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.48-52